Molecular identification of mumps virus genotypes from clinical samples: Standardized method of analysis - Palacios, Gustavo (2005)
Fil: Palacios, Gustavo. Columbia University. Jerome L. and Dawn Greene Infectious Disease Laboratory; Estados Unidos.